Hysteresis‐Suppressed High‐Efficiency Flexible Perovskite Solar Cells Using Solid‐State Ionic‐Liquids for Effective Electron Transport. Issue 26 (4th May 2016) - Yang, Dong; Yang, Ruixia; Ren, Xiaodong; Zhu, Xuejie; Yang, Zhou; Li, Can; Liu, Shengzhong (Frank)
Abstract : An efficiency of flexible perovskite solar cells (Pvs‐SCs) of 16.09% is achieved, the highest value reported for flexible Pvs‐SCs to date. The outstanding performance is attributed to the superior features of alternative electron‐transport materials, such as antireflection, a suitable work function, high electron mobility, and a reduced trap‐state density of the perovskite material.